Clinical Mastitis in Small Ruminants Referred to a Veterinary Teaching Hospital: 23 Cases - Gabriel Inácio Brito; Liz de Albuquerque Cerqueira; Simone Perecmanis; José Renato Junqueira Borges; Márcio Botelho de Castro; Antonio Carlos Lopes Câmara (Microorganisms, 2025)
Clinical mastitis in small ruminants is usually seen with an incidence of less than 5% and most cases, especially with hyperacute evolution, are not referred for hospital care. During the 5-year survey, 16 goats and 7 sheep, totaling 23 small ruminants, met the inclusion criteria with a definitive diagnosis of clinical mastitis. Clinical signs ranged greatly among cases, varying from septic state in hyperacute cases, and enlarged, pendulous udder associated with chronic pain and abnormal gait in chronic cases. Microbiological culture revealed a wide array of bacterial pathogens, including Staphylococcus aureus, Escherichia coli, Streptococcus spp., and Pasteurella spp. In vitro antimicrobial susceptibility profiles varied greatly among bacteria isolates, ranging from sensitive to all tested antimicrobials to a multi-resistant profile. Pathological features included hyperemia and dark red areas of necrosis in the skin, marked hyperemia of the affected gland at the cut surface, lactiferous ducts and gland cisterns filled by cloudy or suppurative fluid, abscesses, and hardness of the mammary gland parenchyma. This retrospective study highlights the multifactorial nature and clinical variability of mastitis in small ruminants, demonstrating its significant impact on animal health, welfare, and production.